A rare occurrence of progressive encephalomyelitis with rigidity and myoclonus in a case of breast carcinoma on treatment: a case report - Gubbala, Rajani; P., Arumugam; C., Nikhileshwar Reddy; K., Sanath; Pathi, Nikhil; Rajappa, Senthil J. (International Journal of Research in Medical Sciences, 2025)
Progressive encephalomyelitis with rigidity and myoclonus (PERM) is a subtype of Stiff-Person syndrome (SPS) and it is characterized by progressive muscle rigidity, painful spasms, and stimulus sensitive abnormal involuntary movements (myoclonus). PERM is distinct from classical SPS in view of its more rapid progression, additional neurological symptoms, and poorer prognosis. It is an autoimmune-mediated disorder of the central nervous system (CNS), particularly affecting inhibitory pathways and can present as a paraneoplastic syndrome. We present the case of a 65-year-old woman with metastatic breast cancer who initially presented with spasmodic abdominal contractions misdiagnosed as intractable hiccups. Her symptoms progressed to include jaw stiffness, dysarthria, dysphagia, and generalized myoclonus, requiring invasive mechanical ventilation. Investigations showed normal brain imaging, unremarkable cerebrospinal fluid analysis, and positive amphiphysin antibodies in paraneoplastic encephalitis panel thus confirming PERM. She was treated with methylprednisolone (500 mg/day for 5 days) followed by intravenous immunoglobulin (IVIG) (2 g/kg over 5 days), resulting in complete resolution of symptoms and ventilator weaning. This case highlights the importance of recognizing PERM in cancer patients and demonstrates the potential efficacy of immunotherapy in its management.